2002
DOI: 10.1109/tpwrs.2002.805016
|View full text |Cite
|
Sign up to set email alerts
|

Power system stability agents using robust wide area control

Abstract: Conventional power system stabilizers (PSSs) are major local damping controllers acting through generator excitation systems. There are studies that suggest that remote signals could increase damping beyond that attainable by local signals. In this paper, a supervisory level power system stabilizer (SPSS) using wide area measurements is proposed. The robustness of the proposed controller is capable of compensating for the nonlinear dynamic operation of power systems and uncertain disturbances. The coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Однією з перших ігор, яка побудована на основі мультиагентних систем, вважають гру "Pacman" ( Heydt , & Mili, 2002). Мета гри полягає у збиранні їжі в лабіринті, при цьому потрібно уникати зустрічі з ворогами.…”
Section: огляд наявних імітаційних моделейunclassified
See 2 more Smart Citations
“…Однією з перших ігор, яка побудована на основі мультиагентних систем, вважають гру "Pacman" ( Heydt , & Mili, 2002). Мета гри полягає у збиранні їжі в лабіринті, при цьому потрібно уникати зустрічі з ворогами.…”
Section: огляд наявних імітаційних моделейunclassified
“…"Fifa" -це імітація футбольної гри, де гравців комунікують між собою і передають м'яч один одному, ціллю гри є забити м'яч у ворота суперника. Порівняно із грою "Pacman", складність мультиагентних алгоритмів в "Fifa" набагато вища, що забезпечила високий рівень комунікації агентів, можливість зміни рівнів складності та багатьох інших додаткових властивостей імітаційної системи (Ni, Heydt, & Mili, 2002). Хоча і в імітаційній моделі, яку використовують у "Fifa", є недоліки, одним з таких -є вузька сфера прийняття рішень агентів, що робить агентів примітивними та прогнозованими.…”
Section: огляд наявних імітаційних моделейunclassified
See 1 more Smart Citation
“…The use of a centralized control, utilizing information of synchronized phasor measurement systems, has been proposed in several works [30], [6], [32], [33], [28]. The data from the PMUs (Phasor Measurement Units) can be used to produce the controller input and a central controller, that can be the PDC (Phasor Data Concentrator), generates the control signals sent to the generators under the central control.…”
Section: B Design Of a Centralized Controllermentioning
confidence: 99%
“…through synchronized measurements enabled by the GPS satellites. It has been shown that by using the remote signals the controller can enhance the damping of inter area oscillations and improve the overall dynamic performance of the power system [4]. A new PSS using two signals, the first to dampen the local mode in the area and the second, global signal, to dampen inter-area modes, is proposed in [5].…”
Section: Introductionmentioning
confidence: 99%